Hubungan antara kecanduan internet (internet addiction) dengan fear of missing out (FoMO) pada mahasiswa FK UNSRAT angkatan 2021 - Manumpil, Euphemia; David, Lydia Edmay Viveca; Pali, Cicilia (Jurnal Kedokteran Komunitas dan Tropik, 2023)
Background: The rapid development of technology in the current era of modern digitalization has a huge impact on human life. One of them is the internet which makes it easier to find information and communicate. Despite its benefits, the internet can cause addiction which has negative impacts such as depression, anxiety, dysfunctional cognitive control and other health problems. Internet Addiction is a dependence on the Internet characterized by increased activity and duration of use. FoMO is characterized by feelings of fear of missing out on valuable time with other people. Several studies have stated that there is a link between internet addiction and FoMO. This research aims to determine the relationship between internet addiction and FoMO in Faculty of Medicine UNSRAT Class of 2021 students.Method: The research carried out was a quantitative study with a cross sectional research design and used the Spearman rank correlation test on 275 students of Faculty of Medicine UNSRAT Class of 2021.Results: In the Spearman Rank correlation test, the results obtained were that there was a relationship between internet addiction and FoMO with a value of p=0.000 (p<0.05) and a correlation coefficient of 0.255. The level of internet addiction among students is mostly at a medium level, namely at a percentage of 65.1%. The student's FoMO level is also at a medium level, namely 76.7%.Conclusion: There is a correlation between internet addiction and Fear of Missing Out (FoMO) in Faculty of medicine UNSRAT class of 2021 students with a weak correlation level.Keywords: Internet addiction, fear of missing out (FoMO), medical students